ETIKA BISNIS ISLAM DALAM PERSPEKTIF PEMIKIRAN AL-GHAZALI - Muhayatsyah, Ali (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2020)
Al-Ghazali's views on economy and business are not limited to philosophical plains, but are a combination of real conditions that occur in society with philosophical values, accompanied by logical arguments. Al-Ghazali in his thoughts about business economics is based on the Sufism approach which he wrote in his book Ihya 'Ulum al-Din. As a matter of fact, there are still many practices of tadlis (unknown to one party), namely violating the principle of â€œan taraddin minkumâ€. The practice of tadlis occurs because of four things, namely quantity reduction of the scale; quality, namely the concealment of object defects; price engineering takes advantage of market price ignorance; uncertainty of delivery time, namely the seller does not know for sure the goods will be delivered to the buyer. In addition, we often encounter market engineering practices. Al-Ghazali paid considerable attention to economic and business activities in society, including the utility hierarchy and its characteristics in the corridor of social obligations to social welfare (maslahah). In addition, al-Ghazali views the ultimate goal is salvation. Work is part of worship is evidence of the work ethic created through extrarelgious efforts. That the intention of someone's behavior in accordance with Divine rules in every economic activity can be of worship value. Al-Ghazali has a view of market ethics that emphasizes truth and honesty, which can be applied to market evolution and the role of money based on the ethics and morals of the perpetrators. Al-Ghazali argued that the state must create security conditions to enhance prosperity and economic development. The existence of state institutions, to monitor adverse market practices. Al-Ghazali stated that trade activities are essential to the functionalization of the economy, the need for secure and safe trade routes, and the state should provide protection so that markets can expand and the economy can grow. Keywords: Islamic Business Ethics, Maslahah, Work Ethics. Abstrak Pandangan al-Ghazali mengenai ekonomi dan bisnis tidak terbatas pada dataran filosofis, melainkan perpaduan antara kondisi riil yang terjadi dalam masyarakat dengan nilai-nilai filosofis, disertai argumen yang logis. Al-Ghazali dalam pemikirannya seputar ekonomi bisnis didasarkan pada pendekatan tasawuf yang beliau tuangkan dalam karyanya kitab Ihya â€™Ulum al-Din. Sebagaimana fakta yang terjadi praktek bisnis masih banyak terjadi praktek tadlis (unknown to one party) yaitu melanggar prinsip â€œan taraddin minkumâ€. Praktek tadlis terjadi karena empat hal, kuantitas yaitu pengurangan timbangan; kualitas yaitu penyembunyian kecacatan obyek; rekayasa harga memanfaatkan ketidaktahuan harga pasar; ketidakpastian waktu penyerahan yaitu penjual tidak mengetahui secara pasti barang akan diserahkan kepada pembeli. Selain itu juga sering kita jumpai praktek rekayasa pasar. Al-Ghazali memberikan perhatian yang cukup besar terhadap aktivitas ekonomi dan bisnis dalam masyarakat, termasuk hierarki utilitas dan karakteristiknya dalam koridor kewajiban sosial terhadap kesejahteraan sosial (maslahah). Selain itu al-Ghazali memandang tujuan akhir adalah keselamatan. Bekerja merupakan bagian dari ibadah merupakan bukti etos kerja yang diciptakan melalui upaya ekstrarelgius. Bahwa niat perilaku seseorang yang sesuai dengan aturan Ilahi dalam setiap aktivitas ekonomi dapat bernilai Ibadah. Al-Ghazali mempunyai pandangan tentang etika pasar yang menitikberatkan pada kebenaran dan kejujuran, yang dapat diaplikasikan pada evolusi pasar dan peranan uang berdasarkan etika dan moral para pelakunya. Al-Ghazali berpendapat negara harus menciptakan kondisi keamanan untuk meningkatkan kemakmuran dan pembangunan ekonomi. Eksistensi kelembagaan negara, untuk mengawasi praktek-praktek pasar yang merugikan. Al-Ghazali menyatakan bahwa kegiatan perdagangan merupakan hal yang esensial terhadap fungsionalisasi perekonomian, perlunya rute perdagangan yang terjamin dan aman, serta negara seharusnya memberikan perlindungan, sehingga pasar dapat meluas dan ekonomi dapat tumbuh. Kata kunci: Etika Bisnis Islam, Maslahah, Etos Kerja.